Do you not know any of the "principles of limits"?
Just about any textbook, after it introduces the definition of limits, quickly gives:
\(\displaystyle \lim_{x\to a} (f(x)+ g(x))= \lim_{x\to a} f(x)+ \lim_{x\to a} g(x)\)
\(\displaystyle \lim_{x\to a} (f(x)- g(x))= \lim_{x\to a} f(x)- \lim_{x\to a} g(x)\)
\(\displaystyle \lim_{x\to a} (f(x)g(x))= \left(\lim_{x\to a} f(x)\right)\left(\lim_{x\to a} g(x)\right)\)
\(\displaystyle \lim_{x\to a} \frac{f(x)}{g(x)}= \frac{\lim_{x\to a} f(x)}{\lim_{x\to a} g(x)}\)
provided \(\displaystyle \lim_{x\to a} g(x)\ne 0\)
Those very easily give you the solution to this problem.